Brucella spp. and Francisella tularensis from an invasive alien species (Sus scrofa) in the southcentral USA. Issue 3 (24th March 2021) - Peper, Steven T.; Hoffarth, Anna; Athanasiou, Kevin; Hawkins, Samuel L.; Wilson‐Fallon, Alexander N.; Gibson, Anna; Reinoso Webb, Cynthia; Gaskamp, Joshua A.; Webb, Stephen L.; Haydett, Katelyn M.; Tiffin, Hannah S.; Presley, Steven M.
Abstract: Wild pig ( Sus scrofa ) populations in the United States are expanding and increasing in distribution and abundance and are known to reservoir a variety of pathogens that can have economic and agricultural impacts. We examined wild pigs for exposure to Brucella spp. and Francisella tularensis from Oklahoma and Texas to determine their potential role as a regional reservoir for these pathogens since wild pigs co‐occur with livestock, especially on rangelands in this region. Antibodies to Brucella spp. and F. tularensis were found in every location sampled and during multiple years. Overall, wild pigs had a 12.5% prevalence of Brucella spp. and a 14.8% prevalence of F. tularensis in this study. Wild pig prevalence of Brucella spp. was 43 times higher in southcentral Oklahoma compared to previously published results. Understanding and monitoring regional disease prevalence rates in wild pigs are necessary, especially on rangelands managing for livestock that may be susceptible to these diseases.